Ultrawideband Radar - Taylor, James (CRC Press, 2017)
Providing a practical review of the latest technology in the field, Ultrawideband Radar Applications and Design presents cutting-edge advances in theory, design, and practical applications of ultrawideband (UWB) radar. This book features contributions from an international team of experts to help readers learn about a wide range of UWB topics, including: History of the technology American and European governmental regulations and key definitions Nonsinusoidal wave propagation theory Random signal radar Object detection by ground permittivity measurements Large-target backscattering effects Medical applications Large current radiator antenna design Materials-penetrating theory Radar signal processing Weak-signal detection methods Holographic and real time radar imaging This book's contributors use practical information to illustrate the latest theoretical developments and demonstrate UWB radar principles through case studies. Radar system engineers will find ideas for precision electronic sensing systems for use in medical, security, industrial, construction, and geophysical applications, as well as those used in archeological, forensic and transportation operations.